Pengaruh Keputusan Investasi PerusahaanTerhadap Kinerja Perusahaan Dengan Arus Kas Sebagai Variabel Moderasi - Hermanto Hermanto; Andrew Andrew (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This study aims to provide assistance on the relationship between investment decisions and company performance in food and beverage subsector companies with cash flow as a moderating variable. The data for this study utilizes information on food and beverage subsector companies listed on the Indonesia Stock Exchange (IDX) for 5 research year periods, from 2018 to 2022 with the amount of information used, namely 40 data from 8 food and beverage subsector entities after using purposive sampling. Samples with secondary data types. The results of the study show that there is a positive influence from most of the investment decision proxies used, namely the growth rate of total assets, CAPTA, and the investment index have a positive effect on ROA as a proxy for company performance and there is a negative effect of fixed asset growth rates on ROA. Cash flow was able to strengthen the CAPTA and the investment index and weaken the growth rate of total assets and growth rate of total assets. The results of disclosing the variable growth rate of total assets, CAPTA, and investment index can be used as a consideration in making investment decisions that can improve company performance.